Case report: Eyelid symptoms as an early harbinger of staphylococcal scalded skin syndrome: a novel pattern of disease onset - Troisi, Mario; Troisi, Salvatore; Mauro, Carolina; Timpone, Laura; D’Aponte, Antonella; Costagliola, Ciro; Strianese, Diego (Frontiers in Ophthalmology, 2025)
BackgroundStaphylococcal scalded skin syndrome (SSSS) is a rare but potentially life- threatening condition caused by exfoliative toxin-producing Staphylococcus aureus. Ocular involvement, although infrequently reported, may lead to vision-threatening complications if not promptly recognized.MethodsThe clinical history, findings, therapy, and outcome of two patients with SSSS exhibiting prominent ocular manifestations at disease onset were analyzed and reported. A comprehensive literature review was performed using PubMed/Medline, Embase, and Scopus incorporating search terms such as “Staphylococcal scalded skin syndrome,” “eye,” “eyelid,” “conjunctival,” “ocular manifestations,” and “ocular adnexal.”ResultsTwo pediatric patients with SSSS were identified. Case 1: a 4-year-old boy with initial blepharitis progressing to periocular scaling, conjunctival inflammation, and corneal staining, confirmed as SSSS by clinical findings and microbiology. Case 2: a 38-month-old boy presenting with bilateral eyelid edema, periocular desquamation, and perioral lesions, with negative corneal staining. Both patients were treated with systemic antistaphylococcal antibiotics (including toxin-targeting regimens) and topical ocular therapy (fusidic acid gel and hypochlorous acid spray), resulting in rapid clinical improvement and complete resolution of ocular and cutaneous lesions. The literature review identified a single reported case of a healthy adult with purulent conjunctivitis as an initial manifestation of SSSS.ConclusionAlthough rare, ocular manifestations may serve as an early indicator of SSSS. Prompt ophthalmological evaluation and combined systemic and targeted topical therapy are essential to prevent ocular sequelae. Awareness of this condition among ophthalmologists and pediatricians is critical to prevent complications and potential permanent visual impairment.